P279 Feasibility of an 8-week out-patient inspiratory muscle training (IMT) programme in patients with interstitial lung disease (ILD). (15th November 2016) - Koulopoulou, M; Greenwood, S; Reilly, C; Chua, F
Abstract : Introduction: The 2013 ATS/ERS guidelines on Pulmonary Rehabilitation suggest that IMT confers significant improvements in various outcomes in chronic obstructive pulmonary disease (COPD). IMT may play a role in dyspnoea and exercise tolerance in patients with ILD; Feasibility of delivering an outpatient IMT programme for ILD is yet to be determined. Aim: The aim of this pilot-feasibility study was to assess the acceptability and practicality of delivering an outpatient IMT programme in patients with ILD. Methods: Radomised trial recruited 17 patients with ILD from St George's Hospital chest clinic, London. Inclusion criteria were: ILD patients on stable medical treatment, with breathlessness MRC >3. 9 patients (intervention group); median (IQR) DLco predicted 44 [28, 45]% underwent H-IMT; exercised at 60% of sustained maximal inspiratory pressure (SMIP); 8 patients (control group) median (IQR) DLco 39.5 [24, 60]% underwent low intensity IMT (S-IMT); exercised at 15% of SMIP. Data collection included pre-post IMT in the following outcomes: six minute walk test (6MWT), quality of life (SGRQ-I), dyspnoea: (Borg and Dyspnoea-12), maximal inspiratory pressure (MIP) and sniff nasal inspiratory pressure (Sniff-P). Results: 76 patients were screened; 26 meet the criteria to participate. 19 (75%) consented to partake in the study. Completion rates for HIIMT was 89% (8/9), and 75% (6/8) for LIMT. HI-IMT-G exhibited significantly higher MIP compared to LI-IMT-G (p = 0.043).There were no significant between-group differences in the other parameters. Within group analysis demonstrated that: HI-IMT improved significantly on 6MWT, MIP, Sniff-P, and SGRQ-I. LI-IMT, improved significantly on 6MWT, Borg and D-12 (Table 1 ). Conclusions: HI-IMT was well tolerated and accepted by ILD patients, and it demonstrated improvements in measured outcomes; IMT requires close monitoring and input to enhance motivation; this type of training can only fit small groups of patients and the extra cost should be considered. IMT may be an alternative option to exercise training for ILD patients to ameliorate dyspnoea and combat exercise deconditioning; larger studies are required to explore effectiveness and cost effectiveness of IMT in ILD.